Luta pela posse da terra em uma região de fronteira: Toledo/PR - Oliveira, Nilton Marques de (2021)
The micro-Toledo, located in the West of Paraná, is regarded as a frontier region, holds large rural area, whose lands are recognized as being among the best in the world in terms of fertility and productivity. In view of this, the present study aimed to analyze the agrarian conflicts in that region, with reference to the period 1960-1970. We analyzed the Crime Criminal Records of the District of Toledo (1960-1970) and the records of the Núcleo de Documentação e Pesquisa (NDP) of the Unioeste/Campus Toledo, confirming the occurrence of many conflicts over land, which showed the existence of a dispute between the owners of power against: settlers, squatters and land grabbers. It was concluded therefore that of the suffering of the peasant was not portrayed in the official history of Toledo, which was highlighted in only the "great men", or those who had conditions to manipulate justice in your favor